284 Cancer risk among tetrafluoroethylene (TFE) synthesis and polymerisation workers. (11th October 2013) - Consonni, D C; Straif,; Symons,; Tomenson,; Van, Amelsvoort; Sleeuwenhoek,; Cherrie,; Bonetti,; Colombo,; Farrar,; Carugno,; Bertazzi,
Abstract : Objectives: Tetrafluoroethylene (TFE), a compound used for the production of fluorinated polymers including polytetrafluoroethylene (PTFE), increases liver and kidney cancer and leukaemia incidence in rats and mice. This is the first time the cancer risk in humans is comprehensively explored in a cohort mortality study. Methods: The study included all current PTFE production sites in Europe (Germany, Italy, The Netherlands and UK) and USA (New Jersey and West Virginia). The study cohort included workers ever employed in the period 1950–2002. A job-exposure matrix (1950–2002) was developed for TFE and ammonium perfluoro-octanoate (APFO), a chemical used in the polymerisation process. For each worker we calculated cumulative exposure to TFE and APFO. The mortality ascertainment covered the period 1950–2008. Standardised mortality ratios (SMR) and 95% confidence intervals (CI) were calculated using national mortality rates as reference. Results: Among 4, 773 workers ever exposed to TFE, we found lower SMRs from most causes of death and increased SMRs for cancer of the liver (SMR 1.27; 95% CI: 0.55, 2.51; 8 deaths) and kidney (SMR 1.44; 95% CI: 0.69, 2.65; 10 deaths), and for leukaemia (SMR 1.48; 95% CI: 0.77, 2.59; 12 deaths). A non-significant upward trend (P = 0.24) by cumulative exposure to TFE was observed for liver cancer. TFE and APFO exposures were highly correlated, therefore their separate effects could not be disentangled. Conclusions: The pattern of findings in this large study substantially narrows the range of uncertainty on the possible cancer risk entailed by working in TFE synthesis and polymerisation, and justifies continuing efforts to minimise exposure, which has already dropped considerably over the years. However, the findings could neither conclusively confirm nor refute the hypothesis that TFE poses a carcinogenic risk to human beings. If a cancer hazard exists, then the risk is small, even in workers with relatively high exposure.